Modelling Lowe syndrome and Dent-2 disease using zebrafish - Lowe, Martin (Frontiers in Cell and Developmental Biology, 2025)
Lowe syndrome and Dent-2 disease are caused by mutations in the gene encoding OCRL, an inositol 5-phosphatase. The phenotype manifests in the eyes, brain and kidney, with the extra-renal features milder in the case of Dent-2 disease. Zebrafish has been used to study OCRL function in vivo and to successfully model these two rare genetic conditions. OCRL-deficient zebrafish have neurodevelopmental defects, which may lie downstream of disrupted endosomal trafficking or primary cilia function. OCRL-deficient zebrafish also have a renal tubular phenotype, with defective endocytosis, abnormal lysosomal function, and shortening of the renal tubule. These defects can account for the low molecular weight proteinuria seen in Lowe syndrome and Dent-2 disease and may explain the other renal features seen in both conditions. Chemical and genetic rescue experiments indicate that zebrafish can be used to test potential therapeutic approaches for Lowe syndrome and Dent-2 disease, raising the possibility of a phenotypic screen for these conditions in zebrafish. Alongside other models, zebrafish has proven its worth in studying Lowe syndrome and Dent-2 disease and should continue to serve as a valuable model going forwards.